The application of environmental isotopes to conceptualize groundwater recharge in a coastal aquifer system: Case study of the West Coast Aquifer System, South Africa. (December 2021) - Andries, C.W.; Kanyerere, T.; Israel, S.; Butler, M.
Abstract: Knowledge of natural recharge mechanisms of the West Coast Aquifer is vital for the implementation of water resource management strategies, which would secure groundwater resources for the region. The analysis of stable ( 2 H and 18 O) and radioactive ( 3 H and 14 C) environmental isotopes have been employed to identify the source of recharge and residence times of the shallow, confined and bedrock aquifers based on sampling conducted during 2017 and 2018. The δ 18 O values for groundwater ranged from −4.34 and 0.65‰ while δ 2 H values ranged from −18.8 and 6.8‰. Groundwater 3 H activity ranged from 0.0 to 1.2 T.U, rainwater tritium was 1.4 T.U while 14 C contents ranged from 0.0 to 1.2pMC. The stable isotope signatures revealed four water groups: non-evaporative shallow and deep groundwater with similar isotopic composition indicating same source of recharge; bedrock groundwater with enriched isotopic signature which show evaporation effect indicating recharge from precipitation where clay lenses are locally absent; non-evaporative shallow groundwater indicate recently infiltrated water; groundwater is not recharged by surface water when drought conditions persist. Deep groundwater in the low-plain discharge zone is recharged by seawater intrusion which is evidenced elevated chloride concentration (35700 mg/l) and enriched stable isotope composition. High tritium (>0.8 T.U) containing groundwater were found downgradient from recharge area, which confirms recent active recharge occurs a distance from postulated recharge area. Tritiated bedrock groundwater with older 14 C ages had the same δ 18 O values as younger shallow groundwater which is consistent with it being derived from locally from low altitudes. The calculated carbon-14 residence times suggest aquifers were recharged under different climatic conditions during cooler periods of the late Pleistocene and Holocene (~2717–33000). The calculated radiocarbon age reflected in the tritium containing groundwater in the deep aquifer supports active localized recharge to deep groundwater system via focused mechanism. The application of environmental isotope methodology combined with an understanding of geology in the study area led to the development of a coherent conceptual flow model. Highlights: Dominant recharge mechanism that occur in the unconfined aquifer is direct recharge via piston flow. Groundwater is not recharged by the Berg River when drought occurs, although it does recharge groundwater when in flood. Groundwater at the lagoon is detached from the WCAS and was recharged under different climatic condition. Groundwater in the confined aquifer is recharged indirectly by downward leakage from the unconfined aquifer. Conceptual model developed illustrating the main recharge mechanism to aquifer units of the WCAS.